Analisis Paro Hidup (Half-Life) dan Keusangan Literatur pada Artikel Jurnal Simbur Cahaya Fakultas Hukum Universitas Sriwijaya Periode Tahun 2018-2022 - Vitriana, Novita; Safitri, Rts. Tiara Hilda; Febrianti, Beta Ria (IAIN Ponorogo, 2024)
This research aims to understand the degree of obsolescence of the literature cited in each Simbur Cahaya Journal article in 2018-2022 and the level of up-to-date information summarized in the Simbur Cahaya Journal seen from the half-life of the literature in the documents cited in 2018-2022. This research uses descriptive research methods with a quantitative approach. Sampling uses a total sampling technique, or the total population is an example. The data was taken from the bibliography or bibliography list contained in the Simbur Cahaya Journal articles for 2018-2022, where every year is published twice (June - December) with 92 article titles, which are analyzed using bibliometric analysis using the law of obsolescence and half-life which is a technique calculation of document obsolescence seen from the half-life level of a piece of literature. The research results show that most of the literature used by the Simbur Cahaya Journal is older than their half-life. For the half-life of the Simbur Cahaya Journal of 5 years, the period from 2018 to 2022 is 17.2 years. It can be concluded that the Simbur Cahaya Journal of the Faculty of Law, Sriwijaya University for 2018-2022 complies with the guidelines of Minister of Education and Culture Regulation Number 22 of 2011 concerning Scientific Periodicals and can be used as a reference for other written works. Keywords: Level of Literature Obsolescence; Update of Information; Bibliometrics